The Effect of Responsiveness and Efficiency on customer Satisfaction of Bank Syariah Indonesia (BSI) at Thursina Hospital in Duri City - Dama Mustika (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
This study aims to determine the effect of responsiveness and efficiency on customer satisfaction of Bank Syariah Indonesia (BSI) at Thursina Hospital in Duri City.This study uses quantitative associative causal relationship (cause and effect). The population of this study were BSI customers at the hospital. Thursina as many as 111 customers. The sampling technique used purposive sampling totaling 87 respondents. Data collection techniques in this study using questionnaires and literature (library study). The data analysis method uses multiple linear regression analysis with IBM SPSS Statistic Version 22 software. The results of this study indicate that responsiveness has a positive effect on customer satisfaction with a significancy  0,000  0,05. While efficiency has a positive effect on customer satisfaction with a sigificancy 0,001 0,05.